A study on windows emulator for Linux platform / Siti Rapizah Snin - Snin, Siti Rapizah (2004)
Due to the resource hungry nature of Microsoft products and its ruthless licensing practices, many computer users are slowly moving away from them and many others are seriously planning to switch to other free systems. However, the perception that alternative systems such as Linux lack in user friendly or productive application packages such as Notepad, Paint and Access, stops them from making an operating system switch. This means that such users will certainly be willing to try out an alternative operating system if an easy mechanism will let them continue to run their favourite packages without any restrictions in the new system. That is, a user on non- Windows platforms should be able to run popular programs such as Notepad and certain games alongside normal Linux programs. The class of products that allows to running a Windows programs on a different operating system platform is called Windows emulator. This project is applied to solve that problem. Here, we will study investigate the implementation of windows emulator. This emulator will enable Windows application software to run on Linux system machine. From the implementation, Windows application software is now freely run on Linux platform by using Wine as a connector.